The Technical Feasibility of Digital Spatial Profiling in Immune/Inflammation Study of Thrombosis - Jiang J; Liu Y (Dove Medical Press, 2023)
Jianjun Jiang, Yang Liu Department of General Surgery, Vascular Surgery, Qilu Hospital of Shandong University, Jinan, Shandong, People's Republic of ChinaCorrespondence: Yang Liu, Department of General Surgery, Vascular Surgery, Qilu Hospital of Shandong University, Jinan, Shandong, 250012, People's Republic of China, Tel +86 18560088317, Email liuyang_sdu@126.comBackground: A comprehensive study of the distribution and role of immune/inflammatory cells in thrombosis is still lacking because traditional pathology techniques cannot accomplish the analysis of numerous protein and genetic data simultaneously. We aimed to evaluate the feasibility of digital spatial profiling (DSP) to study immune/inflammation reaction in thrombosis progression.Methods and Results: An 82-year-old male patient underwent iliofemoral thrombectomy at our institution. The white, mixed and red thrombi were fixed in formalin, dehydrated in ethanol and embedded in paraffin, which were incubated with morphology-labeled fluorescent antibodies (CD45, SYTO13) and the entire target mixture in GeoMx Whole Transcriptome Atlas panel. DSP system was applied to investigate the regions of interest from fluorescence imaging. Fluorescence imaging showed infiltration of immune/inflammation cells in white, mixed and red thrombosis. Whole genome sequencing revealed 16 genes differentially expressed. Pathway enrichment analysis revealed that these genes were significantly enriched in ligand binding and uptake related signaling pathways of the scavenger receptor. The distribution of immune/inflammation cell subsets was different in white, mixed and red thrombosis. The abundance of endothelial cells, CD8 naive T cells, and macrophages in red thrombosis was significantly higher than in mixed and white thrombosis.Conclusion: The results showed that DSP can facilitate efficient analysis using very few thrombosis samples and provide valuable new leads, suggesting that DSP may be a viable and important new tool to study thrombosis and inflammation.Keywords: digital spatial profiling, immune/inflammation cell, arterial thrombosis, whole genome sequencing, scavenger receptor